Vpliv aplikacije botulinskega toksina v plantarne flektorne mišice stopala na vzorec hoje pri otrocih s cerebralno paralizo - Krajnik, Janez (Rehabilitacija (Ljubljana), 2010)
Background: The use of botulinum toxin (BT) for spasticity alleviation in children with cerebral palsy (CP) is a well-established clinical practice at the University Rehabilitation Institute in Ljubljana. Its main objective is to improve impaired gait in children with hemiparetic and diparetic CP before the adolescence. The aim of this paper is to present methods used in the evaluation of application of BT. Methods: Effects of BT were evaluated by clinical testing of musculoskeletal system and gait measurement with an optoelectronic system (Vicon MX), including also two force plates and a surface EMG from 10 most important muscles of the lower limbs. Measurements and analyses were performed one week before TB injection and 6 weeks after TB injection. Results: Illustrative results of analyses performed on two hemiparetic children are presented. One case illustrates a fairly successful treatment while the other shows only minor changes in gait pattern after application of BT. Conclusion: The effects of therapies were rather diverse. We suppose that children with poor function of plantar flexor muscles are having different level of impairments of deeper layer of muscles for plantar flexion and peroneal group, which are known to have important function in foot control and movement.
Keywords: botulinski toksin; cerebralna paraliza; child; hoja; klinično testiranje; otroci; spastičnost; učinki